Head‐up tilt does not enhance prostate tumor perfusion or oxygenation in young rats - Kunkel, Olivia N.; Rand, Taylor A.; Pyle, Joseph G.; Baumfalk, Dryden R.; Horn, Andrew G.; Opoku‐Acheampong, Alexander B.; Ade, Carl J.; Musch, Timothy I.; Ramsey, Michael W.; Delp, Michael D.; Behnke, Bradley J. (Physiological reports, 2022)
Solid tumors contain hypoxic regions that contribute to anticancer therapy resistance. Thus, mitigating tumor hypoxia may enhance the efficacy of radiation therapy which is commonly utilized for patients with prostate cancer. Increasing perfusion pressure in the prostate with head‐up tilt (HUT) may augment prostate tumor perfusion and decrease hypoxia. The purpose of this study was to determine if an increase in the vascular hydrostatic gradient via 70° HUT increases tumor perfusion and decreases tumor hypoxia in a preclinical orthotopic model of prostate cancer. Male Copenhagen rats (n = 17) were orthotopically injected with Dunning R‐3327 (AT‐1) prostate adenocarcinoma cells to induce prostate tumors. After tumors were established, prostate tumor perfusion and hypoxia were measured in rats during level (0°) and 70° HUT positions. To compare the magnitude of the hydrostatic column to that present in humans, ultrasound was used to measure the heart to prostate distance in male human subjects to estimate the prostate vascular hydrostatic pressure with the upright posture. In young rats, no differences were detected in prostate tumor perfusion or prostate tumor hypoxia with 70° HUT versus the level position. However, from the retrospective study, young rats increased prostate vascular resistance to HUT, whereas aged rats lacked this response. Tumor vessels co‐opted from existing functional vasculature in young rats may be sufficient to negate increases in perfusion pressure with HUT seen in aged rats. Additionally, in humans, the estimated hydrostatic column at the level of the prostate is five times greater than that of the rat. Therefore, 70° HUT may elicit increases in prostate/prostate tumor blood flow in humans that is not seen in rats. Blood flow is largely dependent on perfusion pressure, which can be manipulated by body position. Here, we tested the hypothesis that, with head‐up tilt, the increased hydrostatic pressure in orthotopic prostate tumors would increase tumor blood flow. Despite slightly elevated perfusion pressures, we did not observe significant increases in tumor blood flow or reductions in hypoxia.